Development of Marketing Strategies Using Social Media to Increase Business Sales of Amai Desu Cake Products Among Students in the Industry 4.0 Era - Sehli Harnisa; Hera Anis Kartika; Fransiska Yolanda; Messy Wahyuni; Eko Risdianto (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2023)
Marketing strategy is a form of planning found in the field of marketing. In general, marketing is a social process by which individuals and groups get what they need and want by creating and exchanging products and value with other individuals and groups. Data analysis techniques in research use quantitative descriptive analysis techniques. The data collection technique used in this study was using questionnaire sheets that were distributed directly to 10 respondents. This research was conducted at the University of Bengkulu in March. In this study, the factors or variables used for data collection are social media used, culinary variations offered, target customers / marketing, and turnover. In the study, variable X is the selection of social media, information updates, response to buyers and quality and price, while variable Y is an increase in sales of Amai Desu Cake products. After the distribution of questionnaires to find out opinions, perceptions about Amai Desu Cake (ADC) products. In accordance with the results of the distribution of questionnaires, the response of 10 respondents to amai desu cake (ADC) products received 80%, where this category is located in the criteria for delicious. Based on the results of data processing as a whole factors or variables can be accepted, that social media has a role and benefits in increasing the marketing of Amai Desu Cake (ADC) products or increasing the value of turnover, besides that based on the processed data it can also be concluded that all variables X (selection of social media, information updates, response to buyers and quality and price) have a positive effect on variable Y (culinary business marketing).